OPTIMIZATION IN QUALITY OF SERVICE FOR LTE NETWORK USING BANDWIDTH EXPANSION - Fadli Sirait; Akhmad Wahyu Dani; Yuliza Yuliza; Ulil Albab (Universitas Mercu Buana, 2019)
QoS (Quality of Service) of LTE networks can bring the providers to provide broadband services with high performance to end user. Furthermore, the expected data rate transfer is up to 300 Mbit/s per user while the range of bandwidth varies from 1.4 MHz to 20 MHz. The network worked in 1800 MHz bands, 64 QAM modulation technique and used 10 MHz and 15 MHz channel bandwidth. There is a congestion problem for LTE network with 10 MHz channel bandwidth due to high utilization. The paper tries to analyze the QoS parameters, named Key Performance Indicators (KPI) for LTE Networks to solve the problem using bandwidth expansion. The KPIs parameter that is measured by drive test is accessibility, retainability, PRB downlink utilization, and user number. Based on the KPIs measurements results, it is showed that the proposed method to expand the bandwidth from 10 MHz to 15 MHz can avoid congestion problem and impact on improving the performance of LTE network.